Maximizing drilling performance through enhanced solid control system - Irawan, S. (Institute of Physics Publishing, 2017)
High solid content in drilling mud may affect its properties and result in uncertainties at downhole condition. It eventually contributes to poor rig operation performance and operating cost. This research focus on developing solid control system that is suit for drilling 12.25-inch hole. The first part discussed the performance of Rate of Penetration (ROP), Equivalent Circulating Density (ECD) and drill string drag while the second part of the research discussed about the effect of solid control system performance to mud properties Plastic Viscosity (PV), Yield Point (YP) and Low-Gravity Solid (LGS). The input parameters were gathered from two different set up of solid control systems that were used in Well A and Well B. The result is mainly based on the performance of original solid control system new design versus old design. Installation of distributor tank and channel the mud to respective shale shakers significantly enhanced the system and operational performance. The ROP at 12.25-inch drilling were improved by 20. New design improved average the ECD margin by reducing additional pressure exerted using original mud from 4.9 to 2.9. High ECD margin is not recommended because it can break the weak formation. Mud properties while drilling the 12.25-inch hole section; PV, YP and LGS values were improved by 14 , 17 and 25 respectively. Proper mud flow control and routing system at new develop design of solid control system effectively removed the solid in the drilling fluid. This improvement minimizes the tendency of frequent mud flow, screen mesh plugging and tool wear issue. Mud properties such PV, YP and LGS were maintained with an acceptable mud design envelope. © Published under licence by IOP Publishing Ltd.